Determining the mechanism for calculating the tension of a working conveyor belt during a change in the transportation length - Gavryukov, Alexandr; Kolesnikov, Mykhailo; Zapryvoda, Andrii; Lutsenko, Vadym; Bondarchuk, Olga (Eastern-European Journal of Enterprise Technologies, 2024)
This paper examines the working process of a belt conveyor with a working drive that can change the length of transportation. The conveyor can be used for tunneling, development of minerals in mines and quarries, transportation of materials in warehouses. The use of such a conveyor makes it possible to reduce the time for operations to increase or decrease the length of transportation, to exclude reloaders between the working equipment and conveyor itself from the transport chain. It was established that when changing the length of transportation of a working conveyor, the static and dynamic load on the belt increases. The change in the static load of the belt on the drum of the mobile station depends on the speed of the mobile station and the speed of the beltgenerated by the conveyor drive. The dynamic loading on the belt depends on the acceleration of the belt, which is related to the acceleration of the mobile station during the change in the length of the conveyor. For a working conveyor that changes the length of transportation, the static tension of the belt on the drum of the mobile station can increase by 1.1–1.4 times from the initial one. The dynamic loading of the belt can have a significant increase if the acceleration of the mobile station is not stretched over time and acquires large values. Based on the dependencesderived in the current work, a calculation procedure is proposed for the design of a belt conveyor with a working drive that can change the length of transportation. The Mathcad software was applied to verify the designcalculation procedure. The results make it possible to employ new design methods in the construction of competitive machines equipped with a belt conveyor with a variable length of transportation